Boomburbs the rise of America's accidental cities - Lang, Robert, 1959- (James A. Johnson metro series., 2007)
"Addresses the issue of 'boomburbs,' large suburbs of more than 100,000 residents, and examines who lives in them, what drives their development, and how they are governed. Explains why America's suburbs are thriving and how they are shaping the lives of millions of residents"--Provided by publisher.